Modeling of exothermic synthesis of composite with oxide inclusions; MATEC Web of Conferences; Vol. 115 : XXXIII Siberian Thermophysical Seminar (STS-33) - Knyazeva A. G. Anna Georgievna (2017, 2017)
Title screen